Characterization of secondary metabolites produced during interaction of Pseudomonas fluorescens with Fusarium oxysporum - SHARMA, DEEPIKA; GUPTA, MONI; GUPTA, SACHIN; JAGLAN, SUNDEEP; MALLICK, S A (The Indian Journal of Agricultural Sciences, 2019)
Characterization of the Secondary Metabolites (SM) produced by Pseudomonas fluorescens (NAIMCC-B-00361) while growing in mixed culture conditions with fungal pathogen Fusarium oxysporum (NAIMCC-F-00811) was done to better mimic antagonism and interaction in a natural environment. Nutrient media, viz. King’s B Broth (KBB), Potato Dextrose Broth (PDB), Pigment Production Medium (PPM), Czapek Dox broth Medium (CDB) and half minimal media (50% KBB and 50% PDB) were assessed and KBB was found to be the best medium for the production of these metabolites. Antifungal assay of crude metabolite extract was done using poison food technique and the results showed that the crude chloroform extract of metabolites (mixed culture of P. fluorescens and F. oxysporum) grown in KBB medium showed 50.47% inhibition of mycelial growth of F. oxysporum followed by the chloroform extract of solo culture of P. fluorescens which showed 45.38% inhibition of mycelial growth of Bipolaris oryzae. Antibacterial assay of crude metabolite extract was done using Agar well diffusion technique and the results revealed that the crude chloroform extract of mixed culture of P. fluorescens and F. oxysporum grown in KBB medium showed 25.67 mm zone of inhibition against Bacillus subtilis, whereas the extract of solo culture of P. fluorescens showed 18.67 mm zone of inhibition against Klebsella pneumoniae. The qualitative confirmation of antibiotic production by solo culture of P. fluorescens and mixed culture using TLC revealed the presence of antibiotics, i.e. 2, 4-DAPG, pyrrolnitrin and phenazine. HPLC analysis of crude chloroform extract of SM produced by solo culture of P. fluorescens and mixed culture showed the presence of 2,4-DAPG at retention time 20.707 and 20.698 respectively.